PENGARUH PEMBERIAN AROMATERAPI JAHE TERHADAP PENURUNAN EMESIS GRAVIDARUM PADA IBU HAMIL TRIMESTER PERTAMA DI WILAYAH KERJA PUSKESMAS MANGARABOMBANG KABUPATEN TAKALAR - Wirda, Wirda; Ernawati, Ernawati; Oktaviana, Dina; Suardi, Suardi; Nofia, Nofia (Universitas Islam Negeri Alauddin Makassar, 2020)
Background: According to WHO, hyperemesis gravidarum occurs worldwide with an incidence rate of 12.5% of all pregnancies. The incidence of hyperemesis gravidarum in Indonesia is 1-3% of all pregnancies. The Ministry of Health (2015) explains that more than 80% of pregnant women in Indonesia experience excessive nausea and vomiting, which can cause pregnant women to avoid avoiding certain types of food and will pose risks to themselves and the fetus they are carrying. Purpose: to determine the effect of ginger aroma therapy on reducing emesis gravidarum in pregnant women in the first trimester. Design: This study used a Quasy experimental one-group pretest-posttets design using purposive sampling with a sample of 10 people, data collection was carried out through interviews with assessment through the observation sheet pre and post frequency of nausea and vomiting. Results: Based on the results of the study using the Wicoxon test showed that there was an effect of the use of ginger Aroma therapy on reducing emesis gravidarum in pregnant women in the first trimester with a value of p = 0.041 <α 0.05. Conclusion This shows that statistically there is an effect of giving ginger aroma therapy on reducing emesis gravidarum in pregnant women in the first trimester of the Work Area of the Mangarabombang Public Health Center, Takalar Regency 2020.Keywords: (Ginger aromatherapy, Emesis gravidarum, frequency of nausea and vomiting, pregnant women)